Yield, silage quality, and feeding preference of late‐summer sown pearl millet (Cenchrus americanus (L.) Morrone) in Southern Kyushu - Genki Ishigaki; Mitsuhiro Niimi; Hikaru Shigedomi; Yuuto Sasaki; Sachiko Idota; Yasuyuki Ishii (Grassland Research)
Abstract Background Pearl millet is characterized by its high dry matter (DM) yields with a high moisture content, which makes it difficult to process as silage. Methods Pearl millet was sown in mid‐September for 3 years to examine its growth, DM yields in early December, and decrease in DM percentage after frost exposure. The crop was processed as round‐bale silage to assess silage quality and preference by breeding beef cattle. Results Plants reached a height of 160–200 cm, with heading tiller percentages of 50%–70% in early December. With frost exposure, DM percentage increased in leaves and panicles, followed by stems, reaching over 40%, 1 month after exposure. These increases were positively correlated with cumulative frost exposure. After frost exposure, in vitro DM digestibility and crude protein content declined while acid detergent fiber content increased. Repeated cafeteria feeding experiments showed a reduced preference for either pearl millet silage or Italian ryegrass hay. The silage showed moderate acidity at pH 4.73–5.40, with lactic acid at 0.58%–1.62% DM, acetic acid at 0.03%–0.10% DM, and negligible butyric acid, indicating a satisfactory quality. Conclusions In Southern Kyushu, pearl millet sown in late summer can be processed into low‐moisture round‐bale silage in January, the year following sowing.